Zur Ökonomik von Spitzenleistungen im internationalen Sport - Büch, Martin-Peter; Maennig, Wolfgang; Schulke, Hans-Jürgen (Edition HWWI, 2012)
Sport - in particular high-performance sport - is a fascination that is used as a platform for societal concerns. This is the base for different interests in active and passive sports and the state's interest in top-class sport. In most countries, top-class sport is a national concern: states train their athletes in national training centres, support their sports associations in international competitions or promote applications for major sporting events.The articles in this volume provide a well-founded insight into the organisation of high-performance sport and show the different paths of selected countries.